PENERBITAN PEMBERITAHUAN PERKEMBANGAN HASIL PENYIDIKAN (SP2HP) ONLINE SEBAGAI UPAYA TRANSPARANSI POLRI DALAM PENYIDIKAN TINDAK PIDANA (STUDI DI POLRESTABES MEDAN) - Hendra Eko Triyulianto; Madiasa Ablisar; Sunarmi Sunarmi; Mahmud Mulyadi (USU LAW JOURNAL, 2018)
ABSTRACT Efforts to issue a Notice of Progress of Investigation Result (SP2HP) to support the Police service in the field of investigation for Professional, Modern and Promoter starting from the ranks of the Central Police to the Region are expected to improve themselves as soon as possible. Implementation of Promoter program should be implemented immediately considering that the Police must provide optimum guidance and service to the community. Especially in the current digital era where information and communication systems are fundamental and important elements. Today people are beginning to feel that the role of Information and Communication Technology has slowly replaced human roles in various aspects of life, various business activities, government, and education began to be replaced with e-business, e-government, and e-education, slowly the role of Information and Communication Technology has brought lifestyle to the digital age. Police-ranks are also required to be able to adapt to the role of information technology, where in this digital era of accountability, effectiveness, and efficiency is absolutely necessary. The main problem in this research is about the lack of public confidence in the performance of Police investigators in conducting criminal investigations reported to him. In Polrestabes Medan, a program / application of SP2HP Online publication has been created which aims to enable the public to easily access all information related to the police report made. However, the application is insufficient, because it is related to the lack of personnel support, inadequate financial support, and the support of facilities and infrastructure that are still self-supporting, plus the use of the application method is still missing and has not been taught to each of the Sector Police below Polrestabes Medan.   Keywords   :     Issuance of Online Progress Result (SP2HP) Notification; Police Transparency Efforts in Crime Investigation; Polrestabes Medan.